Conceptualising valuation quality in practice: a valuer perspective. Issue 3 (3rd July 2021) - Amidu, Abdul-Rasheed; Levy, Deborah; Bolomope, Muhammed
ABSTRACT: Valuation quality is a complex, multifaceted construct deeply embedded within curriculum and the standards documents of property valuation professional practice, yet explicit discussion of how the concept is currently understood and approached within the valuation process is lacking in literature. The aim of this study is to contribute to the interpretation of valuation quality by exploring how it is conceptualised from the perspective of valuers in practice. Drawing on 19 semi-structured, in-depth interviews, the study explores the experiences of practising valuers, active in the cities of Auckland and Wellington, New Zealand. The findings provide insights into four important quality indicators: professionalism; effective and customised communication; reporting accuracy; and compliance obligations, which accommodate the practical meaning of valuation quality and enable a nuanced understanding of the various behaviours or acts (e.g., production of readable report and telling a clear story of process) and objects (e.g., aesthetic, collaborations and standards) that firms and individuals create and rely on to produce quality in practice. These insights can provide the basis for a robust description of valuers' expectation and the development of a framework for valuation quality to enhance valuer training and professional development. Future research should focused on how these quality indicators match up to the client's expectations.